Arrow-Fisher-Hanemann-Henry and Dixit-Pindyck option values under strategic interactions - FUJII, Tomoki (Institutional Knowledge at Singapore Management University, 2011)
We extend the Arrow-Fisher-Hanemann-Henry (AFHH) and Dixit-Pindyck (DP) option values to game situations. By reinterpreting the AFHH option value as a change in the surplus from conservation because of the prospect of future information, we deal with the conceptual diﬃculty associated with the AFHH option value in the presence of strategic interactions. We then introduce the DP option value into a game situation. We show that the equivalence between the expected value of information and the DP option value in the standard model does not hold under strategic interactions.